Plant microRNAs regulate the defense response against pathogens - Luo, Changxin; Bashir, Nawaz Haider; Li, Zhumei; Liu, Chao; Shi, Yumei; Chu, Honglong (Frontiers in Microbiology, 2024)
MicroRNAs (miRNAs) are a class of small non-coding RNAs, typically 20-25 nucleotides in length, that play a crucial role in regulating gene expression posttranscriptionally. They are involved in various biological processes such as plant growth, development, stress response, and hormone signaling pathways. Plants interact with microbes through multiple mechanisms, including mutually beneficial symbiotic relationships and complex defense strategies against pathogen invasions. These defense strategies encompass physical barriers, biochemical defenses, signal recognition and transduction, as well as systemic acquired resistance. MiRNAs play a central role in regulating the plant's innate immune response, activating or suppressing the transcription of specific genes that are directly involved in the plant's defense mechanisms against pathogens. Notably, miRNAs respond to pathogen attacks by modulating the balance of plant hormones such as salicylic acid, jasmonic acid, and ethylene, which are key in activating plant defense mechanisms. Moreover, miRNAs can cross boundaries into fungal and bacterial cells, performing cross-kingdom RNA silencing that enhances the plant's disease resistance. Despite the complex and diverse roles of miRNAs in plant defense, further research into their function in plant-pathogen interactions is essential. This review summarizes the critical role of miRNAs in plant defense against pathogens, which is crucial for elucidating how miRNAs control plant defense mechanisms.